Răspuns :
Răspuns:
Explicație pas cu pas:
E(x) = (3x-2)²-(x - 2)² + (x-1)(x + 1)-2x(4x - 1) =>
E(x) = (3x-2-x+2)(3x-2+x-2) + x²-1-8x²+2x =>
E(x) = 2x·(4x-4) -7x²+2x-1 =>
E(x) = 8x²-7x²-8x+2x-1 =>
E(x) = x²-6x-1
----------------
minima lui E(x) este pentru x = 3
(x = -6/(-2·1) = 3)=>
E(3) = 3²-6·3-1 = 9-18-1 = -10 =>
E(x) ≥ -10 pentru ∀ x ∈ R
-------------
sau
x²-6x-1 ≥ -10 <=>
x²-6x+9 ≥ 0 <=>
(x-3)² ≥ 0 ceea ce este adevarat pentru ∀ x ∈ R =>
E(x) ≥ -10 pentru ∀ x ∈ R
Explicație pas cu pas:
[tex]E(x) = {(3x - 2)}^{2} - {(x - 2)}^{2} + (x - 1)(x + 1) - 2x(4x - 1) = \\ [/tex]
[tex]= 9 {x}^{2} - 12x + 4 - ( {x}^{2} - 4x + 4) + ( {x}^{2} - 1) - (8 {x}^{2} - 2x) \\ [/tex]
[tex]= 9 {x}^{2} - 12x + 4 - {x}^{2} + 4x - 4 + {x}^{2} - 1 - 8 {x}^{2} + 2x \\ [/tex]
[tex]= 10 {x}^{2} - 9 {x}^{2} + 6x - 12x + 4 - 5[/tex]
[tex]= {x}^{2} - 6x - 1 = {x}^{2} - 6x + 9 - 10[/tex]
[tex]= {(x - 3)}^{2} - 10[/tex]
[tex]{(x - 3)}^{2} \geqslant 0 \iff {(x - 3)}^{2} - 10 \geqslant - 10 \\[/tex]
[tex]\implies E(x) \geqslant - 10[/tex]
q.e.d.